2018
DOI: 10.1056/nejmoa1802917
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Trial of Ibrutinib plus Rituximab in Waldenström’s Macroglobulinemia

Abstract: Among patients with Waldenström's macroglobulinemia, the use of ibrutinib-rituximab resulted in significantly higher rates of progression-free survival than the use of placebo-rituximab, both among those who had received no previous treatment and among those with disease recurrence. Atrial fibrillation and hypertension were more common with ibrutinib-rituximab, whereas infusion reactions and IgM flare were more common with placebo-rituximab. (Funded by Pharmacyclics and Janssen Research and Development; Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
270
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 308 publications
(289 citation statements)
references
References 27 publications
13
270
0
6
Order By: Relevance
“…Recently, the phase III randomized trial comparing ibrutinib plus rituximab or placebo plus rituximab showed a longer PFS in patients treated with the combination (82% vs 28% at 30 months) . After a median follow‐up of 26.5 months, the best response rate resulted significantly higher with the combination treatment (92% vs 47%, P < 0.001).…”
Section: Monoclonal Gammopathy Of Undetermined Significance (Mgus)mentioning
confidence: 99%
“…Recently, the phase III randomized trial comparing ibrutinib plus rituximab or placebo plus rituximab showed a longer PFS in patients treated with the combination (82% vs 28% at 30 months) . After a median follow‐up of 26.5 months, the best response rate resulted significantly higher with the combination treatment (92% vs 47%, P < 0.001).…”
Section: Monoclonal Gammopathy Of Undetermined Significance (Mgus)mentioning
confidence: 99%
“…The current meta‐analysis involves mostly patients receiving chemoimmunotherapy or anti‐CD20 monoclonal antibodies. Many novel agents for the treatment of hematological malignancies have been developed in the past decade and have shown promising results . The risk of HBV reactivation with these agents is currently unknown, and hence we usually monitor HBV DNA levels regularly during treatment so that we can rapidly implement preemptive antiviral treatment at the first sign of reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The small molecule Bruton's tyrosine kinase (BTK) inhibitors, for example, ibrutinib, have shown promising results in the treatment of lymphoma and chronic lymphocytic leukemia . These agents block B‐cell antigen receptor signaling, which prevents the growth of malignant B cells and induces apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…There are scant data comparing outcomes between patients treated with rituximab alone or in combination. The recently published INNOVATE study showed deeper responses and higher 30‐month PFS rates with the combination of ibrutinib and rituximab versus placebo and rituximab (Dimopoulos et al , ). However, in this large randomized study, no OS difference could be detected between the groups.…”
Section: Clinical Characteristics At Diagnosis and At Primary Therapymentioning
confidence: 99%
“…With a 10‐year OS rate of 86% in young WM patients, one could argue that OS might not be an optimal outcome of interest in these patients. Not surprisingly, OS benefits have not been apparent with any intervention in population‐based or randomized studies (Olszewski et al , ; Dimopoulos et al , ). Despite the limitations of this study (i.e.…”
Section: Clinical Characteristics At Diagnosis and At Primary Therapymentioning
confidence: 99%